Rasio Penutupan Luka pada Tikus Diabetes Diinduksi Streptozotocin dengan Perlakuan Dressing Tipe Pasif dan Interaktif (Penelitian Pendahuluan) - Eko Naning Sofyanita; Arya Iswara (Poltekkes Kemenkes Semarang, 2021)
Deparaffinization is a stage before the staining process to remove/dissolve paraffin so that the absorption of color in tissue preparations is maximized. Deparaffinization is usually carried out using xylol and toluol. Xylol has toxic effects including acute neurotoxicity, heart and kidney damage, hepatotoxicity, fatal blood dyscrasias, skin erythema, dry skin, peeling skin, and also has a carcinogenic effect. The toxicity effect of olive oil is lower than that of xylol. Oils that have non-polar properties can remove the remaining paraffin contained in the tissue. The purpose of this study was to determine the microscopic appearance of the kidney tissue preparations of mice deparaffinized with olive oil on hematoxylin eosin (HE) staining. The type of research used is experimental research which is analyzed with a descriptive approach. The results of the assessment of preparations deparaffinized with xylol in 80 visual fields obtained 100% good preparations and preparations deparaffinized with olive oil in 80 visual fields obtained 0% poor preparations, 11.3% poor preparations, and 88.7% good preparation. So it can be said that better results are found in the microscopic picture of the kidney preparations of mice (Mus musculus) deparaffinized with xylol.